A Communication Architecture Based on SCTP and SIP to Support Mobile Real-Time Multimedia Applications - Costa, Daniel G.; Fialho, Sergio Vianna (INFOCOMP Journal of Computer Science, 2009)
New versions of SCTP protocol allow the implementation of handover procedures in the transport layer, as well as the supply of a partially reliable communication service. An end-to-end communication architecture is proposed herein, using SCTP with the session initiation protocol, SIP, besides additional protocols. This architecture is intended to handle real-time multimedia applications with mobility requirements. The Specification and Definition Language is used to specify the operation of a control module, which coordinates the operation of the system component protocols. This specification is intended to prevent ambiguities and inconsistencies in the definition of this module, assisting in the correct implementation of this architecture